Non-fundamental expectations and economic fluctuations: Evidence from professional forecasts - Choy, Keen Meng (Institutional Knowledge at Singapore Management University, 2006)
It is theoretically possible that non-fundamental idiosyncratic shocks to agents’ rational expectations are a source of economic fluctuations. Studies using data on consumer and investor sentiment suggest that this is indeed an important source of fluctuations. We present the results of a study that uses forecasts from professional forecasters to extract non-fundamental shocks to expectations. In contrast to previous studies, we show that non-fundamental expectations are not a significant source of output fluctuations, although such shocks contributed to inflation.